#Femvertising à luz da Análise de Discurso: o processo discursivo das campanhas publicitárias direcionadas às mulheres - Voigt, Juliana Karina (2019)
The central interest of this study is to understand the discursive functioning of Femvertising. In the position of analyst, I occupy the role of the imbecile, as Michel Pêcheux appoints, when he shows that we must break with natural reading practices and investigate the process. In analogy to the philosopher's example, my analyst's orientation reserves the focus for the finger, not the moon. It means, i try to understand how the discursive process that anchors Femvertising happens. Born of the union of two terms in English: feminism and advertising, the neologism is understood as the publicity strand that preaches female empowerment, strives for gender equality, and seeks the freedom of women. More than a discursive possibility, the Femvertising is considered, in the contemporary world (in the neoliberal society), a standard to be followed. The production of advertising campaigns for products and services for women underwent a process of adaptation and reformulation and, in the current society, not everything can be said. Campaigns designed and produced by subjects for subjects of the current political-historical context. Female consultancies arise in the consumer market to produce what is considered appropriate for the woman of the 21st century: the woman who consumes, the head of the family, the financially emancipated. The freedom is configured as something desired and possible, from the point of view of the right-holders, who believe, as a consequence of the ideological assumption, that it can be achieved. At the moment of analysis, it was possible to observe that the union of the feminist’s discourse, the chauvinist’s discourse and the capitalist’s discourse authorizes and regulates the emergence of the Femvertising’s discursive formation of, which is formed from already-said, with the proposal to break with speeches and patterns of crystallized behavior, fruits of historical interdiscourse. I observed that although it emerges as a resistance to the past and as a denial of chauvinism, Femvertising is the fruit of this denial, so the resistance of its discourse, to an unconsciously institutionalized command, often generates the effect that this discourse is still obeying his biggest opponent. Femvertising, under the effect of rupturing and symbolically marking the new generation of historical subjects, masks its belonging to the advertising discourse. Thus, determined by the economic command and presenting the characteristics of the advertising discourse, the process of the Femvertisng is analyzed, in the present research, under the non-transparency of the language, the non-evidence of meaning and the ideological subjects. Anchored in studies by Pêcheux (2014), Orlandi (2017), Kehl (2016) and Cattelan (2016), i reflect on the publicity campaigns that contribute to women's empowerment and profit from it